FAO durum wheat database - Gómez Macpherson H.; Marathée J.P. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
The Crop and Grassland Service (AGPC) of FAO is collecting, selecting and organising information on durum wheat. This information will be presented by country and agro-ecological zones within the country in a user-friendly information system. The data will include statistics at country level, a description of institutes working on durum wheat, a description of the agro-ecological zones in which durum wheat is a major crop and a description of the durum wheat cropping systems and varieties grown in each agro-ecological zone. It will be possible to search for entries based on one or more criteria (e.g. country, agro-ecological zone, cropping system, variety, growth duration, use, and biotic and abiotic stresses). The potential clients of the database are interested individuals, organisations and institutions, be they non-governmental, governmental or international.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)